Natural Science Mini Project Practicum through The Practical Instructions Module for Identifying Natural Chemicals in Medicinal Plants - Bakhtiar Ardiansyah; Agus Ramdani; Aliefman Hakim; Muh Makhrus (Postgraduate Program, University of Mataram, 2023)
21st century learning includes achieving the ability to communicate, think critically, think and act creatively, and collaborate. One of the efforts recommended by experts to achieve this is through the application of project-based learning. Various forms of blending are implemented using project-based learning. One form of method in project-based learning is the practicum method. This literature review aims to describe various forms of project-based learning as well as the development of practical guide modules and their relationship to several practical activities that lead to the chemical identification of natural medicinal plant ingredients. The various results of this research will give birth to alternative project-based learning by developing practical guide modules that can strengthen students' understanding of high-level thinking skills related to the classification of living things, especially plants, as well as science process skills and scientific attitudes.